Low Complexity CS/CB Techniques for Aerial Assisted Cellular Network With Imperfect CSI - Sheila N. Mugala; Jonathan Serugunda; Dorothy K. Okello (IEEE Access)
The inclusion of aerial base stations (ABSs) into cellular networks has many potential benefits, including low-cost network connectivity for remote rural areas and quick deployment to provide coverage in emergencies and enhance capacity at hotspots. However, their strong line-of-sight links exacerbate network interference particularly at terrestrial base stations. To mitigate this interference, this paper proposes coordinated scheduling/coordinated beamforming (CS/CB) with low complexity. Through simulations, the performance and complexity for three low complexity beamforming algorithms are compared for a multi antenna aerial assisted cellular network in a rural environment under perfect and imperfect channel state information (CSI) scenarios. The beamforming algorithms are zero forcing beamforming (ZFBF), block diagonalization using singular value decomposition (BD SVD) and block diagonalization using Householder transformation (BD HH). The results show that CS/CB improves coverage over non coordination. For an 8 antenna system the maximum increment in coverage probability for ZFBF is 16% and 44% for cooperating cluster sizes of 3 and 6 respectively against 29% and 42% for the BD techniques. As the CSI error variance increases from 0.1 to 0.3, the coverage probability drops at a rate of 0.6 for ZFBF and 0.2 for the BD techniques while the average rate deteriorates at 6 Mbps for ZFBF and 2 Mbps for the BD techniques. BD HH gives the lowest overall complexity and together with its resilience to CSI error is the most pragmatic beamforming technique for an aerial assisted cellular network.